The Effect of the Slow Stroke Back Massage (Ssbm) Technique on Reducing High Blood Pressure in Hypertension Sufferers in the Working Area of ​​the Purwo Agung Community Health Center, Way Kanan Regency in 2024 - Sasti, Meilany; Erwin, Tubagus; Sulastri, Diah (CV. Rayyan Dwi Bharata, 2024)
The DASH diet serves as a valuable educational tool for managing hypertension, benefiting both patients and their families. This study aimed to assess the impact of education on the DASH (Dietary Approaches to Stop Hypertension) diet on the blood pressure levels of individuals with hypertension within the jurisdiction of the Rumbia Public Health Center in Rumbia District, Central Lampung Regency, during the year 2024. Employing a quantitative research methodology, the study utilized a quasi-experimental design featuring a one-group pre-test and post-test framework. The target population consisted of 353 hypertensive individuals residing in the Rumbia Health Center area from January to April 2024, with a sample size of 62 participants. Data were analyzed using the independent t-test. Findings revealed that the average blood pressure prior to the DASH diet education in the intervention group was 138/78 mmHg, compared to 149/89 mmHg in the control group. Post-education, the intervention group exhibited an average blood pressure of 126/75 mmHg, while the control group showed 136/82 mmHg. The results indicate a significant effect of DASH diet education on blood pressure among hypertensive patients in the Rumbia Health Center area, with a p-value of 0.000. It is recommended that health centers disseminate information regarding the benefits of DASH diet education on blood pressure management through various media, including leaflets, booklets, and posters, positioning it as a viable alternative treatment for individuals with hypertension.